Monitoring biomolecule concentrations in tissue using a wearable droplet microfluidic-based sensor - Adrian M. Nightingale (Nature Portfolio, 2019)
Continuous real-time measurement of biomarker levels in body fluids offers many exciting possibilities. Here, the authors develop an integrated wearable droplet microfluidic sensor that combines continuous sampling of tissue fluid with in situ analysis using wet-chemical assays.